2020
DOI: 10.1021/acs.molpharmaceut.0c00042
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Optimal Molar Ratio in Amino Acid-Based Coamorphous Systems

Abstract: Coamorphous drug formulations are a promising approach to improve solubility and bioavailability of poorly watersoluble drugs. On the basis of theoretical assumptions involving molecular interactions, the 1:1 molar ratio of drug and coformer is frequently used as "the optimal ratio" for a homogeneous coamorphous system (i.e., the coamorphous system with the highest physical stability and, if strong interaction is possible between two molecules, the highest glass transition temperature (T g )). In order to more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 30 publications
4
39
0
Order By: Relevance
“…Similarly, a PCA was performed on the FTIR spectra of freshly prepared carvedilolaspartic acid and carvedilol-glutamic acid CAMS to investigate the spectral differences among CAMS at different molar ratios [72]. Similar-shaped distribution patterns of CAMS were obtained at different molar ratios in the PCA score plots, as those seen in the T g α deviations at different molar ratios (see Section 6.1.2.).…”
Section: Detection Of the Glass Transition Temperatures (T G )mentioning
confidence: 89%
See 3 more Smart Citations
“…Similarly, a PCA was performed on the FTIR spectra of freshly prepared carvedilolaspartic acid and carvedilol-glutamic acid CAMS to investigate the spectral differences among CAMS at different molar ratios [72]. Similar-shaped distribution patterns of CAMS were obtained at different molar ratios in the PCA score plots, as those seen in the T g α deviations at different molar ratios (see Section 6.1.2.).…”
Section: Detection Of the Glass Transition Temperatures (T G )mentioning
confidence: 89%
“…In approximately half of the cases, where the molar ratio was optimized, it was shown that the ideal molar ratio (with respect to physical stability or/and dissolution performance of CAMS) between drug and co-former was not at the equimolar ratio. For example, for the carvedilol and aspartic acid CAMS, it was shown that the 1:1 molar ratio was not the ideal molar ratio for physical stability, even though salt formation between carvedilol and aspartic acid was expected to occur at the equimolar ratio based on the chemical nature of the drug and co-former [72].…”
Section: Molar Ratio Optimization Of Investigated Camsmentioning
confidence: 99%
See 2 more Smart Citations
“…The co-former can interact with the drug through different kinds of molecular interactions which can be divided into non-strong interactions (such as hydrogen bond formation and π-π interactions) and strong interactions (such as ionic interactions) [11][12][13][14]. A method of detecting the optimal mixing ratio of strongly interacting co-amorphous systems was suggested by Liu et al and a method for non-strongly interacting co-amorphous systems was investigated by Kissi et al, but the latter method was experimentally demanding and not widely accessible [6,15]. Therefore, it would be beneficial if another, less complex, method could be developed.…”
Section: Introductionmentioning
confidence: 99%